Prioritas Penghuni Terkait Perawatan Rumah Susun Sederhana Sewa di Surabaya - Edward Gondo Kusuma; Njo Anastasia (Diponegoro University, 2021)
Previous research focused on the conditions, awareness, and priorities of tenants for property maintenance in housing and middle-class flats, so that simple flats have not received special attention related to property maintenance issues. This study aims to determine the maintenance priority, the reasons given by tenants to maintain simple flat, the correlation between maintenance priorities and the reasons for maintain. The method used was a survey by distributing questionnaires. Property maintenance is divided into three such as structure, architecture and utility. The results show that each tenant has different priorities on property maintenance and their reasoning behind it. Disagreements occur in each of the tenants, where some of them are more concerned with maintenance and reasons for utility maintenance rather than structure and architecture maintenance. The more important the maintenance is, the stronger reason to do the maintenance. This research provides benefit to the management, namely the Surabaya City Governement, to develop procedures that can be proposed by tenants to obtain maintenance for damaged flat in accordance with priority needs of tenants. The managers can also develop maintenance strategies before and after damaged occur.